THE IMPACT OF PARENTAL INVOLVEMENT ON STUDENTS' ENGLISH LEARNING ACHIEVEMENT: A STUDY OF MAN MATANGKULI - Arsyad, Hanif; Rasyimah, Rasyimah; Saputra, Edi (English Education Department, 2024)
This study investigates the extent of parental involvement in motivating students to learn English and its impact on their academic achievement in learning the language. The research also seeks to determine the extent to which parents support their children in learning English as a foreign language. Utilizing an experimental research design, this study involved second-year students from MAN Matang Kuli as the population and sample. The experimental and control groups were divided into two classes. A pre-test and post-test were conducted to observe both groups at two-time points. Data were collected through questionnaires, semester report books, and test scores. The study employed statistical analysis to establish causal relationships between parental involvement and students' English achievement, following Borg's (1989) principles for experimental research design. The findings revealed a significant cause-and-effect relationship between parental involvement and students' academic achievement. Higher parental involvement, particularly in their roles as educators and facilitators at home, contributed to better student performance. The mean achievement score (∑y) of students was 64.05, with a standard deviation of 6.5, and the average parental involvement score (X) was 2.4. Additionally, the study highlighted the role of teaching methods and classroom dynamics in supporting students' English learning.The research underscores the importance of parental support and suggests that English teachers adapt teaching strategies to students' conditions and needs. It concludes that students whose parents are less involved in their education tend to perform lower in English subjects.